Plastics and polymers today, some questions, a particular viewpoint - Michel Dumon (Waste Management Bulletin, 2025)
The number of plastic and polymer types are tremendously numerous. At the present time, they fulfill a lot of daily citizen’s needs and economical interests. They appear to be irreplaceable, but they raise questions. The paper is not a case study nor an experimental study but a viewpoint on the fate of plastics. Their situation and evolution are presented in the form of questions where actors and ‘spheres’ correspond to different visions. ‘Spheres’ are industry, ecosystems, waste management, innovation, technologies and citizens. Statistics predict a growing production and consumption of plastics. Thus a dilemma arises between environment and health protection, the well being of citizens, the will of authorities, the will and ability of manufacturers/producers to supply better ‘products’, and the willingness of citizens to change their habits and behaviors towards less plastics.Against overuse and pollution, plastic recycling is stopgap, a subterfuge. Recycling of all fossile-based plastics is an illusion. Bioplastics are very partial substitutes for fossil-based plastics. The future of plastics deals as much as with behaviors, habits and wills rather than materials themselves. A true decrease in the plastics consumption, firstly those used in packaging, is a long-term solution. But, according to most data and figures, fossile synthetic plastics will be produced and used for decades.